The degree of public school teachers’ acceptance of using the blended learning approach in the first three basic grades in the Southern Badia Education Directorate - Al-Mashaqba, Mahmoud Khalaf (Journal of Curriculum and Teaching Methodology, 2024)
The aim of this research is to identify the degree of public school teachers’ acceptance of using the blended learning approach in the first three basic grades in the Zarqa Education Directorate. The research sample consisted of (93) male and female teachers who were selected randomly. To achieve the objectives, the descriptive analytical approach was used based on the questionnaire, which was verified for its validity and reliability. The results indicated that the degree of the respondents’ acceptance of using the blended learning approach was high, and the highest scores were the degree of teachers’ acceptance of using the blended learning approach in terms of expected benefit, followed by ease. expected, and then communication and social communication skills were all at a high level. Finally, the field of available capabilities came in last place, and the degree of approval for it was moderate, There were statistically significant differences at the level between the averages of the teachers’ response scores towards accepting the use of the blended learning approach due to the academic qualifications variable in the area. The expected benefit and the level of significance are less than 0.05 in this area, and there are no statistically significant differences at the level between the averages of teachers’ response scores towards accepting the use of the blended learning approach due to the variable years of experience and the level of significance is greater than 0.05 in all areas. One of the most important obstacles facing teachers when using blended learning is that teachers and students do not have the appropriate tools and techniques, while the most important obstacles that teachers face when using blended learning are: The most common type of Internet connection used to attend electronic classes is (3G), and the research concluded with a number of recommendations and proposals.